Penyuluhan Kesehatan tentang Inisiasi Menyusu Dini (IMD) di Desa Pandai Woha - Nur Fitriyah; Nurlaila Fitriani; Ade Sriwahyungsih (PT.Mantaya Idea Batara, 2022)
Early Initiation of Breastfeeding is the giving of breast milk to the baby in the first hour after birth, where the baby is placed on the mother's chest and allows the baby to find the mother's nipple. Early initiation of breastfeeding is one way to reduce infant mortality. The practice of early initiation of breastfeeding, especially in Indonesia, is still very low. According to the 2002 Indonesian Health Demographic Survey, Early Breastfeeding Initiation in Indonesia is only 3.7%. This service was carried out at the Pandai village polindes in February 2021. This activity aims to increase mother's knowledge about Early Initiation of Breastfeeding and add insight that early initiation of breastfeeding is very important because it is the first step for the success of exclusive breastfeeding. The method of service is by lecture/counseling, discussion and question and answer by explaining the extension material in the form of powerpoint. As a result of our dedication, we got the enthusiasm of active participants in asking questions so that they are committed to trying to carry out Early Breastfeeding Initiation as soon as the baby is born. Participants said their knowledge increased about Early Initiation of Breastfeeding